P121 Latent classes of last-year drug use in a large cross-sectional community-based sample of United Kingdom men who have sex with men. (13th September 2016) - Melendez-Torres, GJ; Bourne, A; Reid, D; Bonell, C; Hickson, F; Weatherburn, P
Abstract : Background: Analyses of drug use in men who have sex with men (MSM) have exclusively focused on examining individual drugs in isolation, and have not examined how different drug use patterns in combination are associated with socio-sexual variables. Understanding these patterns is important in targeting HIV prevention and harm reduction interventions and in developing a fuller picture of drug use patterns in context. We use latent class analysis to develop a typology of recent drug use in MSM, and to explore how the distribution of MSM across latent classes differs by HIV testing history and sexual risk. Methods: We used data from the 2014 Gay Men's Sex Survey, an online community-based survey of MSM in the UK conducted in summer 2014. MSM aged 16 and above and resident in the UK were recruited via a variety of online dating sites and community email bulletins. We constructed a latent class model with manifest indicators corresponding to last year use of: poppers, erectile dysfunction medications, tranquilisers, cannabis, ecstasy, speed, mephedrone, GHB, ketamine, crystal meth and cocaine. We tested associations between HIV testing history and number/type of non-steady sexual partners, and membership in each drug use class. Results: We judged a five-class model to be optimal, with scaled relative entropy of 79.3%. The classes described were 'minimal users' (64.2% of respondents), 'low-threshold users' (14.0%) who mostly used poppers and erectile dysfunction medications, 'old-skool users' (cocaine/ecstasy/poppers) (14.0%), 'new psychoactive substance (NPS) users' (3.1%) with high rates of mephedrone, GHB and crystal meth, and 'polydrug users' (4.7%) with high probabilities of use across all drugs. MSM with multiple non-steady partners in the last year were about twenty times as likely to belong to the class of NPS users and more than seven times as likely to belong to the class of diverse users as compared to MSM with no non-steady partners; similarly, MSM who reported being HIV positive were more than six times as likely to belong to the class of diverse users as MSM whose last test was negative. Discussion: While much attention has been paid to chemsex among MSM, this analysis indicates that men using drugs associated with chemsex are in the minority, and encourages reflection on how harm reduction and HIV prevention services are addressing the needs of men whose drug use clusters differently. This latent class model, like all analyses of its kind, is tentative and should be revisited as drug use changes over time.